Aetiology and surgical treatment of childhood blepharoptosis. Issue 11 (1st November 2002) - Lee, V; Konrad, H; Bunce, C; Nelson, C; Collin, J R O
Abstract : Aims: To describe the aetiology, demography, surgical management, and outcome of a cohort of paediatric ptosis patients in a large tertiary referral oculoplastic centre. Methods: A case note review of all patients undergoing ptosis surgery below the age of 16 years in a tertiary referral oculoplastic unit documenting the laterality, aetiology, severity of ptosis, indications for and type of surgery undertaken, the proportion of good, suboptimal, and poor surgical outcomes, re-operations, and level of patient satisfaction. Results: 340 patients (82% (280/340) unilateral, 18% (60/340) bilateral ptosis) with myogenic (79%, 269/340), aponeurotic (5%, 16/340), neurogenic (11%, 37/340), mechanical (2%, 6/340), apparent (1%, 2/340), and syndrome related (3%, 10/340) ptosis underwent anterior (41%, 141/340) and posterior (26%, 90/340) levator resection, frontalis suspension with mersilene (9%, 29/340) and autogenous fascia lata (17%, 59/340), levator transposition (5%, 15/340) and other surgery (1%, 6/340) for visual (43%, 141/333) and cosmetic (57%, 189/333) indications. 77% (260/340) of patients achieved a good outcome, 10% (35/340) a suboptimal outcome, and 13% (45/340) a poor outcome requiring re-operation. There was no statistically significant difference in surgical outcome between patients with mild, moderate, or severe ptosis and with good, moderate, or poor levator function. The level of recorded patient satisfaction with the surgical outcome was 90% (206/229). Conclusions: Results suggest that most groups of paediatric ptosis patients, including those with poor levator function and severe ptosis, achieve satisfactory results with the appropriate ptosis surgery.